2021
DOI: 10.3390/microorganisms9122467
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas 1-Aminocyclopropane-1-carboxylate (ACC) Deaminase and Its Role in Beneficial Plant-Microbe Interactions

Abstract: The expression of the enzyme 1-aminocylopropane-1-carboxylate (ACC) deaminase, and the consequent modulation of plant ACC and ethylene concentrations, is one of the most important features of plant-associated bacteria. By decreasing plant ACC and ethylene concentrations, ACC deaminase-producing bacteria can overcome some of the deleterious effects of inhibitory levels of ACC and ethylene in various aspects of plant-microbe interactions, as well as plant growth and development (especially under stressful condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 93 publications
(159 reference statements)
2
21
0
Order By: Relevance
“…Similar to our results, Al Hamad et al (2021) have demonstrated that the ACCD-producing Streptomyces griseorubens UAE2 had augmentative BCA effects on royal poinciana plants inoculated with N. dimidiatum compared to S. wuyuanensis UAE1 that did not have ACCD activity. This supports previously published studies reporting that plants inoculated with BCAs possessing ACCD activity can make the plant more resistant to environmental stresses (Wang et al, 2000;El-Tarabily et al, 2019Mathew et al, 2020;Glick and Nascimento, 2021;Jiménez-Mejía et al, 2022) treated with the ACCD-producing Methylobacterium spp. significantly reduced wilt symptoms of Ralstonia solanacearum and lowered the ET emission (Yim et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to our results, Al Hamad et al (2021) have demonstrated that the ACCD-producing Streptomyces griseorubens UAE2 had augmentative BCA effects on royal poinciana plants inoculated with N. dimidiatum compared to S. wuyuanensis UAE1 that did not have ACCD activity. This supports previously published studies reporting that plants inoculated with BCAs possessing ACCD activity can make the plant more resistant to environmental stresses (Wang et al, 2000;El-Tarabily et al, 2019Mathew et al, 2020;Glick and Nascimento, 2021;Jiménez-Mejía et al, 2022) treated with the ACCD-producing Methylobacterium spp. significantly reduced wilt symptoms of Ralstonia solanacearum and lowered the ET emission (Yim et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, ten (five from each SA and NSA) isolates with multiple modes of action were in vitro active against F. solani (Table 1), confirming the importance of actinobacteria as potential BCAs against plant pathogens (Saeed et al, 2017a;Kamil et al, 2018;. It has been reported that inoculation of plants with ACCD-producing microorganisms can ameliorate the effect of environmental (biotic and abiotic) stresses in plants (Glick, 2014;Al Hamad et al, 2021;Glick and Nascimento, 2021;Jiménez-Mejía et al, 2022). In our study, the enzymatic activities of ACCD in these isolates were also measured.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…BLAST searches were performed using SequenceServer v2.0.0 ( 11 ). Strain RGM 3321 harbors one copy of a gene for 1-aminocyclopropane-1-carboxylate (ACC) deaminase ( acdS ), which is involved in the degradation of ACC, a precursor of ethylene in plants ( 12 , 13 ). The strain contains genes for a quinoprotein glucose dehydrogenase ( gcd ) and the pyrroloquinoline quinone ( pqq ) operon ( 14 ), suggesting a mechanism for phosphate solubilization in soil via gluconic acid synthesis ( 15 , 16 ).…”
Section: Announcementmentioning
confidence: 99%